2002
DOI: 10.1002/app.10206
|View full text |Cite
|
Sign up to set email alerts
|

Melting behavior of poly(trimethylene terephthalate)

Abstract: ABSTRACT:In this study, the melting behavior of isothermally crystallized polytrimethylene terephthalate (PTT) was investigated. Multiple melting behaviors in DSC heating trace were found because two populations of lamellar stacks were formed during primary crystallization and the recrystallization at heating process, respectively. This fact could be also confirmed from the result of optical microscopy observation. The Hoffman-Weeks equation was applied to obtain equilibrium melting temperature (T m 0 ). The T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 28 publications
4
82
0
Order By: Relevance
“…Peak III disappears altogether when the crystallization temperature is greater than ca. 194 • C. This triple-melting phenomenon has previously been reported [5]. The occurrence of peak I has been attributed to recrystallization during the re-heating process and peaks II and III to the melting of the primary crystallites of two populations of the lamellar stacks [5].…”
Section: Crystal Modification and Crystallinity Of Pttsupporting
confidence: 64%
See 1 more Smart Citation
“…Peak III disappears altogether when the crystallization temperature is greater than ca. 194 • C. This triple-melting phenomenon has previously been reported [5]. The occurrence of peak I has been attributed to recrystallization during the re-heating process and peaks II and III to the melting of the primary crystallites of two populations of the lamellar stacks [5].…”
Section: Crystal Modification and Crystallinity Of Pttsupporting
confidence: 64%
“…Hence, PTT recrystallization during subsequent heating process. Based on wide-angle X-ray diffraction (WAXD) results, it was suggested that the crystal modification of PTT did not change with crystallization temperature, at least within the temperature range studied [5].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] According to Figure 8, both neat components, in particular PEN, reveal a multiple melting behavior, detected from the appearance of a small shoulder on the main peak assigned to the partial melting of crystallites with different thermodynamic stability. [21,22] Blends of PTT/PEN 92/8 processed at different mixing conditions were investigated in the same manner. NMR measurements have shown that with increasing processing temperature and time the transesterification is more pronounced.…”
Section: Ptt/penmentioning
confidence: 99%
“…7 The equilibrium melting temperature of PTT is about 525 K, and the equilibrium enthalpy of fusion is 28.8 kJ/mol. 11 The isothermal crystallization kinetics of PTT has also investigated by Avrami theory and the crystallite morphology from melt and cold-crystallization exhibited typical negative spherulite and sheaf-like crystallite. 12 Structure development in PTT fibers during drawing has been studied by two groups.…”
Section: 3mentioning
confidence: 99%